If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -12 = 5x + 25 Reorder the terms: -12 + 8x = 5x + 25 Reorder the terms: -12 + 8x = 25 + 5x Solving -12 + 8x = 25 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12 + 8x + -5x = 25 + 5x + -5x Combine like terms: 8x + -5x = 3x -12 + 3x = 25 + 5x + -5x Combine like terms: 5x + -5x = 0 -12 + 3x = 25 + 0 -12 + 3x = 25 Add '12' to each side of the equation. -12 + 12 + 3x = 25 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = 25 + 12 3x = 25 + 12 Combine like terms: 25 + 12 = 37 3x = 37 Divide each side by '3'. x = 12.33333333 Simplifying x = 12.33333333
| 8.1(4.6)= | | 2x+19=9x+6 | | 2x-3+6x-8=5x+4 | | 4/5=9/10 | | 5v-4.2=8.3 | | p-(17)=-23 | | -11x=-6 | | 2x^2=0.08 | | -5/8=3/4=5/8 | | 59=-x/8 | | 4x=a-6 | | 15(x)+85(y)=2556 | | 3(1+-1y)=8+(-5y) | | x^3-6x^2-15x+40=0 | | -5=-27w | | -w/9=-50 | | -2w+5(w-2)=-19 | | -39=3(v+3)+5v | | 9x+4y=10 | | 1/4x1/4x1/4x1/4 | | 3m-12=3(8m+3) | | 8m^2+72m-16=0 | | 5(2z-1)-5(z+9)=2(z+1) | | 3(4a+5)=3+6a | | 6-6n=6(6n+1) | | 2x^2-25x-54=0 | | -7+5x=-7(1+8x) | | 7x-8y=-18 | | ^4√(((3x^8)(y^2))/(8x^2)) | | P^2=81/100 | | 1+2b=-(-5b-8)-2b | | -8(-5-6x)=40-5x |